2016
DOI: 10.4172/2167-0412.1000271
|View full text |Cite
|
Sign up to set email alerts
|

Rice Bran Extracts Inhibit Invasion and Intracellular Replication of Salmonella typhimurium in Mouse and Porcine Intestinal Epithelial Cells

Abstract: Dietary rice bran supplementation has been shown to inhibit Salmonella fecal shedding in animals. The aim of this study was to determine if bran extracts from two distinct rice varieties, Lijiangxintuanheigu (LTH) and Sanhuangzhan-2 (SHZ-2), differentially inhibit Salmonella enterica serovar Typhimurium invasion and intracellular replication. Rice bran extracts were tested in vitro using mouse small intestine epithelial (MSIE) and intestinal porcine epithelial cells (IPEC-J2). Fluorescent labeled Salmonella wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Typhimurium by rice bran was previously investigated across rice varieties in mice [ 9 , 18 ], and these findings are relevant to the present study for chickens as the previous studies compared three different cultivars of rice: Jasmine, Red Wells, and Calrose that were examined as treatment candidates in the current study. The previous studies confirmed variation in secondary metabolite components such as total phenolics, γ-oryzanol, fatty acids and vitamin E isoforms [ 9 , 18 , 19 ]. Jasmine rice has a brown bran layer and has significantly less total phenolic content compared to Red Wells, but is relatively rich compared to other varieties in γ-tocotrienol, a vitamin E isoform with anti-proliferative activity on Caco-2 cells, a human colon cancer cell line [ 19 ].…”
Section: Introductionmentioning
confidence: 84%
“…Typhimurium by rice bran was previously investigated across rice varieties in mice [ 9 , 18 ], and these findings are relevant to the present study for chickens as the previous studies compared three different cultivars of rice: Jasmine, Red Wells, and Calrose that were examined as treatment candidates in the current study. The previous studies confirmed variation in secondary metabolite components such as total phenolics, γ-oryzanol, fatty acids and vitamin E isoforms [ 9 , 18 , 19 ]. Jasmine rice has a brown bran layer and has significantly less total phenolic content compared to Red Wells, but is relatively rich compared to other varieties in γ-tocotrienol, a vitamin E isoform with anti-proliferative activity on Caco-2 cells, a human colon cancer cell line [ 19 ].…”
Section: Introductionmentioning
confidence: 84%
“…and Escherichia coli with minimum inhibitory concentrations as high as 0.976 mg/mL for the V. cholerae strain (Kondo et al 2011). In another study by Ghazi et al (2016), Salmonella enterica subsp. serovar Typhimurium is dose-dependently inhibited by red rice bran extracts in the small intestine epithelial (MSIE) and intestinal porcine epithelial cells (IPEC-J2) in mice.…”
Section: Introductionmentioning
confidence: 93%